2020
DOI: 10.1016/j.cnsns.2020.105275
|View full text |Cite
|
Sign up to set email alerts
|

Excitable dynamics in neural and cardiac systems

Abstract: The application of mathematics, physics and engineering to medical research is continuously growing; interactions among these disciplines have become increasingly important and have contributed to an improved understanding of clinical and biological phenomena, with implications for disease prevention, diagnosis and treatment. This special issue presents examples of this synergy, with a particular focus on the investigation of cardiac and neural excitability.This issue includes 24 original research papers and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Many nonlinear systems exhibit excitable behaviour, whereby they exhibit large-amplitude oscillations in response to small-amplitude, transient perturbations. One prominent example in biology is electrical excitability in cells, which underlies the function of neurons ( Izhikevich, 2000 ; De Maesschalck and Wechselberger, 2015 ; Wedgwood et al, 2021 ), cardiac cells ( Majumder et al, 2018 ; Barrio et al, 2020 ), pituitary cells ( Sanchez-Cardenas et al, 2010 ; Hodson et al, 2012 ) and pancreatic beta cells ( Bertram et al, 2007 ; McKenna et al, 2016 ). Moreover, the the study of these systems is broadly applicable, and such excitable dynamics are also observed in semiconductor lasers ( Terrien et al, 2020 , 2021 ), social media networks ( Mathiesen et al, 2013 ), epidemiology ( Vannucchi and Boccaletti, 2004 ), and wildfires ( Punckt et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many nonlinear systems exhibit excitable behaviour, whereby they exhibit large-amplitude oscillations in response to small-amplitude, transient perturbations. One prominent example in biology is electrical excitability in cells, which underlies the function of neurons ( Izhikevich, 2000 ; De Maesschalck and Wechselberger, 2015 ; Wedgwood et al, 2021 ), cardiac cells ( Majumder et al, 2018 ; Barrio et al, 2020 ), pituitary cells ( Sanchez-Cardenas et al, 2010 ; Hodson et al, 2012 ) and pancreatic beta cells ( Bertram et al, 2007 ; McKenna et al, 2016 ). Moreover, the the study of these systems is broadly applicable, and such excitable dynamics are also observed in semiconductor lasers ( Terrien et al, 2020 , 2021 ), social media networks ( Mathiesen et al, 2013 ), epidemiology ( Vannucchi and Boccaletti, 2004 ), and wildfires ( Punckt et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%